Effects of Acyclovir and IVIG on Behavioral Outcomes after HSV1 CNS Infection - Chandran Ramakrishna; Mari S. Golub; Abby Chiang; Teresa Hong; Markus Kalkum; Edouard M. Cantin (Behavioural Neurology)
Herpes simplex virus 1 (HSV) encephalitis (HSE) has serious neurological complications, involving behavioral and cognitive impairments that cause significant morbidity and a reduced quality of life. We showed that HSE results from dysregulated central nervous system (CNS) inflammatory responses. We hypothesized that CNS inflammation is casually involved in behavioral abnormalities after HSE and that treatment with ACV and pooled human immunoglobulin (IVIG), an immunomodulatory drug, would improve outcomes compared to mice treated with phosphate buffered saline (PBS) or ACV alone. Anxiety levels were high in HSV-infected PBS and ACV-treated mice compared to mice treated with ACV + IVIG, consistent with reports implicating inflammation in anxiety induced by lipopolysaccharide (LPS) or stress. Female, but not male, PBS-treated mice were cognitively impaired, and unexpectedly, ACV was protective, while the inclusion of IVIG surprisingly antagonized ACV’s beneficial effects. Distinct serum proteomic profiles were observed for male and female mice, and the antagonistic effects of ACV and IVIG on behavior were paralleled by similar changes in the serum proteome of ACV- and ACV + IVIG-treated mice. We conclude that inflammation and other factors mediate HSV-induced behavioral impairments and that the effects of ACV and IVIG on behavior involve novel mechanisms.